Catering : - Mattel, Bruce (Wiley, 2016)
This is a significant contrast to other texts which are geared to a specific segment of catering such as on-premise, off-premise, or corporate dining. The graduate who decides to enter into catering will be charged with providing the?restaurant? experience to their clients and optimizing profits for their employer. Catering will assist them in achieving these goals.